2021
DOI: 10.34172/japid.2021.016
|View full text |Cite
|
Sign up to set email alerts
|

CBCT data relevant in treatment planning for immediate maxillary molar implant placement

Abstract: Background. This study used CBCT images to evaluate the suitability of maxillary first and second molar sites to receive immediate implants. Buccopalatal and mesiodistal widths of maxillary molar inter-radicular septum were evaluated at three different levels (crestal, middle, and apical), in addition to assessments of the root apex and furcation proximities to the sinus floor and comparisons of these measurements between the first and second upper molar sites before extraction.Methods. A total of 427 dental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…However, in this study, the FMS-P distance was less than 0.5 mm in both the first and second molars, and the palatal intruded into the sinus in 49% and 30% of the first and second molars, respectively. Other studies have reported similar findings, with palatal root intrusion into the sinus ranging between 29% and 73% and 23% and 69% for first and second molars, respectively [13,18].…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…However, in this study, the FMS-P distance was less than 0.5 mm in both the first and second molars, and the palatal intruded into the sinus in 49% and 30% of the first and second molars, respectively. Other studies have reported similar findings, with palatal root intrusion into the sinus ranging between 29% and 73% and 23% and 69% for first and second molars, respectively [13,18].…”
Section: Discussionsupporting
confidence: 70%
“…Only 37% of the first molars and 35% of the second molars in this study fulfilled these criteria. Similarly, Deporter et al [ 13 ] reported that only 61.7% of maxillary first molars and 34% of second molars are potential candidates for immediate implants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations